2014
DOI: 10.1007/s13238-014-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of helicity of α-helical antimicrobial peptides to improve specificity

Abstract: A major barrier to the use of antimicrobial peptides as antibiotics is the toxicity or ability to lyse eukaryotic cells. In this study, a 26-residue amphipathic α-helical antimicrobial peptide A12L/A20L (Ac-KWKSFLKTFKSLKKTVLHTLLKAISS-amide) was used as the framework to design a series of D- and L-diastereomeric peptides and study the relationships of helicity and biological activities of α-helical antimicrobial peptides. Peptide helicity was measured by circular dichroism spectroscopy and demonstrated to corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 34 publications
11
93
0
2
Order By: Relevance
“…Low pH was found to enhance the activity of both peptides against Escherichia coli , which appeared to involve membrane interaction, but interestingly, although gad-1 and gad-2 were predominantly α-helical at neutral pH, acid conditions led to a large decrease in the levels of α-helicity possessed by these peptides [29]. These results contrast with most α-helical AMPs where an enhanced capacity for membranolysis and antimicrobial activity is generally associated with increased levels of this secondary structure [96,97]. It was proposed that gad-1 and gad-2 each possessed a structural plasticity, which facilitated an appropriate balance between amphiphilic and mixed hydrophobic/hydrophilic structural features that promoted maximal levels of membrane interaction and antibacterial activity [29].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…Low pH was found to enhance the activity of both peptides against Escherichia coli , which appeared to involve membrane interaction, but interestingly, although gad-1 and gad-2 were predominantly α-helical at neutral pH, acid conditions led to a large decrease in the levels of α-helicity possessed by these peptides [29]. These results contrast with most α-helical AMPs where an enhanced capacity for membranolysis and antimicrobial activity is generally associated with increased levels of this secondary structure [96,97]. It was proposed that gad-1 and gad-2 each possessed a structural plasticity, which facilitated an appropriate balance between amphiphilic and mixed hydrophobic/hydrophilic structural features that promoted maximal levels of membrane interaction and antibacterial activity [29].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…[10] Mimicking AMPs with unnatural oligomers [11] can provide artificial analogues that exhibit similar activities with ah igher enzymatic stability and disfavored oligomerization capacities. [16] Current evidence suggests that single l-to-d mutations in all-l sequences lead to decreased helicity and decreased hemolytic activities without affecting the antimicrobial properties. [13,14] An effective solution to these issues may be found in peptide diastereomers, [15] which are commonly used to explore the dependence of biological activities on a-helix formation.…”
mentioning
confidence: 99%
“…HC50 value is the mean concentration of peptide producing 50% hemolysis of freshly isolated human erythrocytes from healthy donors, while MIC is defined as the minimum inhibitory concentration using the microdilution susceptibility test against Escherichia coli. Larger value in therapeutic index indicate greater antimicrobial specificity (Huang et al 2014) that means high in bacteriostatic activity and low in toxicity (Juretic et al 2009a). Therapeutic index value is able to be obtained from experiment (experimental therapeutic index; TIexp) or from software prediction (therapeutic index prediction, TIpred) (Kamech et al 2012).…”
Section: Peptide Sequence and Analysismentioning
confidence: 99%
“…Multiple studies demonstrated that helicity is important for toxicity, antimicrobial activity (Huang et al 2010) and interfacial binding (Fernandez-Vidal 2007) beside physicochemical parameter such as hydrophobicity amphipaticity, charge and sequence also determine antimicrobial activity. It is important in interaction between peptide and microbial membrane (Huang et al 2014).…”
Section: Modellingmentioning
confidence: 99%